IDENTIFICATION OF POTATO PURCHASING BEHAVIORS AND PREFERENCES OF CONSUMERS BY MEANS OF ROBUST FACTOR ANALYSIS - Koksal KARADAS; Ahmet Metin KUMLAY; Ecevit EYDURAN; Ayse KARADAG GURSOY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present questionnaire study was conducted to establish potato purchasing preferences of 385 consumers selected randomly from Igdir, Turkey. All the items ranging from 1 to 11 on the basis of an ordinal 11 point scale data on fresh potato and its products were collected from the consumers. Robust Unweighted Least Squares (RULS) extraction method was used based on promin rotation method for obtaining better solutions in the ordinal data set. Polychoric correlation matrix was used instead of Pearson correlation matrix in the violation of the basic assumption on normal distribution of the ordinal items due to the fact that it is evidence that null hypothesis of multivariate asymmetric kurtosis was rejected (P=0.000). Four new factors were extracted from all the items on both fresh potato and its products through 'Factor' software program, which gives more comprehensive and understandable outputs. The rotated factor loadings for potato products were clustered into four factors: content (Factor 1), value of nutrient and calorie (Factor 2), additives and price (Factor 3) and situation of package and health (Factor 4), respectively. The rotated factor loadings for fresh potato preferences of the consumers were also assigned to four factors: source (Factor 1), price and color (Factor 2), tubers structure (Factor 3) and tubers properties (Factor 4), respectively. The current results revealed that an application of EFA factor analysis on the basis of ULS extraction method, promin rotation method and polychoric correlations as a dispersion matrix was more effective when compared with the traditional EFA applications for the ordinal data. Besides, potato producers, sellers and entrepreneurs who desire to develop new marketing strategies might be recommended to take into account four factors that can affect purchasing preferences of the consumers on fresh potato and its products.